Propuesta de plan de mantenimiento preventivo para la conservación del material Zamak, en las armas traumáticas comercializadas por Lans Soluciones basado en la norma ISO 9001:2015 usando la técnica RCM. (2022)
With the present work a proposal is delivered preventive maintenance plan for conservation of the zamak material (Zn-Al), being common to find a rate high porosity on the surface of traumatic weapons that are exposed to a humid environment such as that of the municipality of Valle del Guamuez/Putumayo, where is the company Lans Soluciones, in charge of the distribution and maintenance of these weapons. The intention is to identify the deterioration of the zamak material caused by the corrosion, using impedance spectroscopy electrochemistry (EIS) and the design of polarization curves power dynamics, allowing to identify the parameters to take into account for the improvement of the plan preventive maintenance that is in force in Lans Solutions, based on the ISO 9001:2015 standard articulated with the RCM technique projecting a organization and proper planning of patient care material obtaining a longer useful life of the weapon traumatic managing to avoid the damages caused by inadequate maintenance that is carried out by not knowing the study material, increasing customer reliability towards the company